2022
DOI: 10.2169/internalmedicine.8976-21
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Hemorrhage in Patients with COVID-19 Undergoing Hemodialysis: Three Case Reports

Abstract: A 73-year-old man receiving hemodialysis and antiplatelets was admitted with a mild case of COVID-19. Heparin was added, and iliopsoas hemorrhage developed. He was successfully treated by interventional radiology. A 76-year-old man receiving hemodialysis and antiplatelets was admitted with mild COVID-19. Heparin was added, and iliacus hemorrhage developed. Despite heparin discontinuation, he died of worsening pneumonia. A 74-year-old man undergoing hemodialysis was admitted with severe COVID-19. Gastrointestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The first symptoms experienced by the patients were primarily respiratory, followed by gastrointestinal symptoms, which is consistent with the findings of previous studies [ 16 , 17 ]. Some studies have reported complications, such as retroperitoneal hemorrhage [ 18 ]. While fever and fatigue were the most common symptoms of early COVID-19 patients [ 19 ], ESKD patients have less fever, which may be due to their immunological aging state [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first symptoms experienced by the patients were primarily respiratory, followed by gastrointestinal symptoms, which is consistent with the findings of previous studies [ 16 , 17 ]. Some studies have reported complications, such as retroperitoneal hemorrhage [ 18 ]. While fever and fatigue were the most common symptoms of early COVID-19 patients [ 19 ], ESKD patients have less fever, which may be due to their immunological aging state [ 20 ].…”
Section: Discussionmentioning
confidence: 99%